Antioxidant activity and mechanism of action of phycocyanin in bulk sunflower oil and respective oil-in-water emulsion - Elham Ehsandoost; Mohammad Hadi Eskandari; Malihe Keramat; Mohammad-Taghi Golmakani (Current Research in Food Science)
This study compared the inhibitory mechanism of phycocyanin in sunflower oil with its activity in a sunflower oil-in-water emulsion. Additionally, the impact of lecithin on the inhibitory mechanism of phycocyanin in sunflower oil was evaluated. A sigmoidal model effectively described the oxidation kinetics. In both sunflower oil and sunflower oil-in-water emulsion, phycocyanin pro-oxidatively attacked lipid hydroperoxides besides inhibiting lipid hydroperoxides. The antioxidant activity of sunflower oil containing phycocyanin and lecithin was 2.2-fold greater than that of sunflower oil containing lecithin alone. The addition of lecithin enhanced the interfacial activity of phycocyanin and altered its hydrogen donating and electron transfer mechanisms. Also, by comparing the reverse micelles size samples of sunflower oil samples containing lecithin, we discovered that lecithin can enhance the potency of phycocyanin by boosting the ability of reverse micelles to incorporate lipid hydroperoxides within their structure.